2021
DOI: 10.1186/s40645-020-00403-6
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution of radiocesium-bearing microparticles over the greater Kanto Region resulting from the Fukushima nuclear accident

Abstract: The Fukushima Daiichi Nuclear Power Plant (FDNPP) accident in March 2011 emitted a considerable amount of radioactive materials. This study isolated radiocesium-bearing microparticles (CsMPs), a form of radioactive materials emitted from the FDNPP at the early stage of the accident, from aerosols collected hourly on filter tapes at seven monitoring stations at the greater Kanto Region, including the Tokyo metropolitan area, on 15 March 2011. The aerosols had a spherical shape ~ 1 μm in diameter with activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Another previous study found eight CsMPs in seven suspended particulate matter monitor filters used on 15 March 2011 (Abe et al 2021). The sample was aspirated using a pump with almost the same flow velocity as that of human breath.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study found eight CsMPs in seven suspended particulate matter monitor filters used on 15 March 2011 (Abe et al 2021). The sample was aspirated using a pump with almost the same flow velocity as that of human breath.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CsMPs can be transported (e.g., as dust in the air, by flowing water, etc. ), resulting in an unpredictable, changing radio-Cs distribution in the environment. Given the existence of CsMPs and their potential long-term impact on the environment and human health, it is essential to detect, evaluate, and differentiate the varying forms of radio-Cs (micro-particle or bulk) found in samples.…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted with permission from ref. [ 227 ] (open access article distributed under the terms of the Creative Commons CC BY license). (b) Identified radioactive plume and reconstructed cloud shine for the in-situ measurements of gamma dose rate obtained at Futatsunuma during the Fukushima accident, between 2:00 UTC, March 14 and 10:00 UTC, March 22, 2011.…”
Section: Source Term and Particle Size Distributionmentioning
confidence: 99%